Socio-psychological determinants of adolescent school engagement - Awang Hashim, Rosna (Universiti Utara Malaysia, 2006)
The study examined a conceptual model integrating existing knowledge on the linkages between life satisfaction,affect, purpose in life, resilience, and school engagement.This model posits direct relationships between all the social psychological variables and school engagement, and also indirect relationships between life satisfaction and school engagement as mediated by all the other variables in the study.Due to the dearth of research on instrument development for use in the local context, the study also developed and validated the Bahasa Melayu measures using the confirmatory factor analytic (CFA) method.Findings established reliability and construct validity of all measures.Additionally, the present study also examined the various school engagement correlates based on some selected demographic variables such as gender, ethnicity, home location, and grade levels.Descriptive statistics indicated that the adolescent respondents were generally engaged in school learning.They generally complied with the requirements of school and classroom, identified with school, but reported relatively lower cognitive engagement. They positively perceived the family, self, school, friends, and their neighbourhood.They showed an inclination towards high positive emotions and low negative emotions. They often thought about their future although they were less confident in achieving their future goals.Finally they also demonstrated having relevant protective factors to adapt competently in the face of adversity, i.e., resilience.Results of the present study demonstrated some demographic differences across the variables and provided support for the proposed model.Girls were more engaged in school learning and thought more often about their future. They were more satisfied with friends and school, but reported higher negative emotions than boys.Boys, on the other hand, reported higher positive emotions and self concept, were more resilient and more satisfied with living in their neighbourhood.Younger adolescents were more satisfied with family, school and neighbourhood, and more behaviourally engaged.However, older adolescents had a clearer purpose in life and were more psychologically engaged in school although they reported higher negative emotions.In terms of home location, rural adolescents were more satisfied with school and their neighbourhood, and more psychologically engaged.With regards to ethnicity, Malays were more satisfied with family and school.Indians reported higher self concept, had clearer purpose in life, were more resilient, exhibited more positive emotions, and thus were more engaged in school learning.Surprisingly, the Chinese were the least satisfied with family, school, and self.In fact, they generally rated lowest on all variables. Other than negative emotions, all variables were positively associated.The strongest relationship was observed between overall life satisfaction and school engagement.All variables were important predictors for school engagement, although the affect components were more prevalent among girls.Affect, purpose in life and resilience mediated the relationship between life satisfaction and school engagement.The mediating model was partially supported. The study supports the adage that “it takes a village to raise a child”.Implications for practice and future research are discussed in the context of engagement in school learning.